Efficacy and safety of sintilimab plus bevacizumab and CAPOX as first-line treatment for patients with RAS-mutant, microsatellite stable, metastatic colorectal cancer - Yanrong Wang; Ru Jia; Haiyan Si; Yue Ma; Mengjiao Fan; Nan Zhang; Fangfang Liu; Yue Shi; Yushan Jia; Yaoyue Zhang; Quanli Han; Zhikuan Wang; et al. (BMC Cancer)
Abstract Background This research aimed to assess the efficacy and safety of combining sintilimab with bevacizumab, oxaliplatin, and capecitabine as a primary therapy for patients with RAS-mutated, microsatellite stable (MSS), and metastatic colorectal cancer (mCRC). Methods In this prospective, open-label, single-arm, phase II trial, eligible patients received up to 8 cycles of capecitabine and oxaliplatin/bevacizumab plus sintilimab, followed by maintenance therapy with capecitabine, bevacizumab, and sintilimab every three weeks until disease progression. Treatment response was evaluated every 2 cycles (6 weeks) according to the Response Evaluation Criteria in Solid Tumors version 1.1. The primary endpoint was ORR, while the secondary endpoints included PFS and AEs. Results The efficacy analysis and safety analysis included 33 patients. The overall response rate was 72.7%, and the median PFS in the full analysis set was 12.9 months (95% CI: 7.5–18.3), and median OS was not reached. Patients with liver metastases demonstrated a higher ORR (20/24 [83.3%]) than those without (4/9 [44.4%], p = 0.073), and the median PFS was 14.7 for patients with liver metastases and 9.6 months for those without (HR: 1.05, 95%CI: 0.34–3.24; p = 0.932). Most immune-related AEs had grades 1–2, and immunotherapy was discontinued in 4 patients due to immune-related AEs. No treatment-related deaths occurred during the study. Conclusions The therapeutic regimen showed encouraging antitumor effects and a favorable safety profile in patients with RAS mutations, MSS, and mCRC, yielding durable results throughout an extended follow-up duration, irrespective of the presence of liver metastases. This research is of great significance because it addresses the limited treatment options in the field of MSS mCRC patients. By providing new treatment strategies or methods, it brings more hope and choices to patients and offers valuable new insights and research directions to the medical community. Clinical trial registration ClinicalTrials.gov: NCT06206096. Registered on May 26, 2021.